2018
DOI: 10.1002/jlb.3a0218-072r
|View full text |Cite
|
Sign up to set email alerts
|

Ascitic fluid regulates the local innate immune response of patients with cirrhosis

Abstract: Ascitic neutrophils from cirrhotic patients with spontaneous bacterial peritonitis (SBP) exhibit an impaired oxidative burst that could facilitate bacterial infection. However, the influence of the cell-free ascitic fluid of these patients on neutrophil function has not been investigated. To analyze this influence, we determined the ascitic levels of cytokines, resistin, and lactoferrin and their association with neutrophil function, disease severity score, and SBP resolution. We analyzed NETosis induction by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
1
11
2
Order By: Relevance
“…The authors argue that the synthesis and secretion of high levels of IL‐10 and IL‐1Ra are synthesized to regulate the inflammatory process . Moreover, in the recent study of Nieto et al a positive correlation between resistin and IL‐1Ra levels and between IL‐1Ra and IL‐6 was observed, levels which coincides with our results, the authors propose that resistin indirectly downregulates neutrophil function through their interaction with macrophages. According to our and previous results, more research is required to elucidate the relationship between the variety of molecules and factors present at the local/systemic microenvironment, and the CAID.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The authors argue that the synthesis and secretion of high levels of IL‐10 and IL‐1Ra are synthesized to regulate the inflammatory process . Moreover, in the recent study of Nieto et al a positive correlation between resistin and IL‐1Ra levels and between IL‐1Ra and IL‐6 was observed, levels which coincides with our results, the authors propose that resistin indirectly downregulates neutrophil function through their interaction with macrophages. According to our and previous results, more research is required to elucidate the relationship between the variety of molecules and factors present at the local/systemic microenvironment, and the CAID.…”
Section: Discussionsupporting
confidence: 91%
“…These results are also similar to those reported by Nieto et al, who observed higher levels of IL‐6 in AF from patients with SBP compared with AF from patients with ASC, the IL‐6 was positively correlated with the percentage of neutrophils in AF. Furthermore, recently the same group have also reported that levels of resistin produced by neutrophils, positively correlates with IL‐6 levels, contributing to the impaired function of neutrophils . Suliman et al also observed higher levels of IL‐6 in both serum and AF from patients with SBP vs patients with ASC, in contrast to our results they also found elevated levels of TNF‐α in their patients, although it is noteworthy that they measured the cytokine concentrations by a different method (ie ELISA).…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations